Diet in the prevention and treatment of depression - systematic review - Szulc, Izabela; Swacha, Weronika; Kozłowska, Julia; Pacek, Katarzyna; Piekarska, Małgorzata; Kasperski, Radosław; Jedlina, Klaudia; Rusin, Klaudia; Budziłło, Julia; Lewandowska, Monika (Journal of Education, Health and Sport, 2023)
Depression is one of the leading causes of disability worldwide. It affects, according to WHO, nearly 300 million people worldwide, a number close to 3,8 % of the world’s population. Depression is not exclusively a mental disorder limited to psychiatry, nowadays it is present in all medical fields. It has a significant association with many comorbidities, as an example cardiovascular diseases and metabolic disorders. Additionally, depression often is manifested with psychosomatic symptoms. Both aspects lead clinicians to major diagnostic and therapeutic challenges. Each one of dietary element: omega-3 fatty acids, zinc, selenium, iron, vitamin B12, vitamin D, folate, creatine was found to correspond with mental health in patients and the level of mentioned diet components is negatively correlated with depression risk of individuals. Each of the dietary aspect considered in the article has a significant correlation with depression disorder and might support the new multidisciplinary attitude toward it in mental health.